Microplastics in the Mondego Estuary and adjacent coastline: Occurrence, characterisation and associated bacterial communities. - Marques, José Luís Clemente (2021)
Dissertação de Mestrado em Bioquímica apresentada à Faculdade de Ciências e Tecnologia